2001
DOI: 10.1152/jappl.2001.91.4.1627
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vivo and in vitro contractile responses to β2-adrenergic receptor stimulation in dogs susceptible to lethal arrhythmias

Abstract: The response to beta-adrenergic receptor (beta-AR) stimulation was evaluated in both isolated cardiomyocytes (video edge detection) and the intact animal (echocardiography) in dogs either susceptible (S) or resistant (R) to ventricular fibrillation induced by a 2-min coronary occlusion during the last minute of exercise. In the intact animal, velocity of circumferential fiber shortening (Vcf) was evaluated both before (n = 27, S = 12 and R = 15) and after myocardial infarction. Before infarction, increasing do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…There was no evidence of impaired global left ventricular structure or function after infarction, as has been previously reported in this model (6,7,22). Left ventricular fractional shortening was unchanged after MI (41 Ϯ 1.6 vs. 40.6 Ϯ 0.9%, baseline and 8 wk post-MI, respectively; P ϭ NS).…”
Section: Resultssupporting
confidence: 79%
“…There was no evidence of impaired global left ventricular structure or function after infarction, as has been previously reported in this model (6,7,22). Left ventricular fractional shortening was unchanged after MI (41 Ϯ 1.6 vs. 40.6 Ϯ 0.9%, baseline and 8 wk post-MI, respectively; P ϭ NS).…”
Section: Resultssupporting
confidence: 79%
“…Work from the Billman laboratory have also demonstrated that exercise training signiWcantly reduced both the in vivo and the in vitro contractile response to 2-adrenergic receptor stimulation in dogs susceptible to ventricular Wbrillation (VT). These studies also showed that 10 weeks of endurance exercise training restored 1-adrenergic receptor expression and protein content in VT susceptible dogs (Billman et al 2006;Holycross et al 2007;Houle et al 2001). Thus, the idea that training mediates its eVects on down regulating 2-adrenergic receptors is an interesting hypothesis that requires further testing.…”
Section: Discussionmentioning
confidence: 90%
“…However, AR2 speci�c adrenergic inotropic responses were attenuated in trained animals [92]. Exercise training has also been reported to attenuate the contractile responses to AR2 stimulation in dogs while restoring AR1 adrenergic receptor protein content [99][100][101]. Whether training exerts its effects on downregulating AR2s is an interesting idea that requires further testing.…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%